A dynamic clinical dental relational database. - Taylor, D.
The traditional approach to relational database design is based on the logical organization of data into a number of related normalized tables. One assumption is that the nature and structure of the data is known at the design stage. In the case of designing a relational database to store historical dental epidemiological data from individual clinical surveys, the structure of the data is not known until the data is presented for inclusion into the database. This paper addresses the issues concerned with the theoretical design of a clinical dynamic database capable of adapting the internal table structure to accommodate clinical survey data, and presents a prototype database application capable of processing, displaying, and querying the dental data.
Keywords: Clinical dynamic database; Clinical survey data; Data logical organization; Data structure; Dental epidemiological data; Dynamic data structure; Internal table structure; Relational database